Courtship and Male-Male interaction behaviour of Orsima ichneumon (Simon, 1901), an Ant-Mimicking jumper spider (Arachnida: Salticidae) - Wee, Renee H.X.; Norma-Rashid, Yusoff; Li, Daiqin; Painting, Christina J. (National University of Singapore, 2017)
This is the first description of male-female courtship and male-male agonistic interactions of Orsima ichneumon (Simon, 1901) jumping spiders. Orsima ichneumon inhabit low shrubs and grasses along sunny forest edges across South East Asia, including Malaysia and Singapore. They are small-medium sized jumping spiders ranging from 5-8 mm in body length, with no obvious sexual size dimorphism. However, there is sexual dimorphism in body shape, most obviously due to a distinct constriction in the male’s abdomen that is less defined in females, and different colouration of the pedipalps. Twenty-eight major behavioural elements were described during intraspecific interactions. Courtship interactions were significantly longer in duration than agonistic interactions, but agonistic interactions were made up of a higher number of behavioural elements. Like most jumping spiders, male O. ichneumon had a more complex behavioural repertoire than females, and displayed their colourful body appendages during courtship and contests. This suggests that females are the choosier sex and there is selection on male ornamentation and signalling behaviour. Our behavioural study will form a useful framework from which to base future work on this colourful species.